Differentiation and stabilisation of the Archean continental crust, the example of the northern edge of the Kaapvaal craton, South Africa - Vezinet, Adrien (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.